The effect of timing and type of exercise on the quality of sleep in trained individuals - Burgess, V.; Antonio, J.; Bland, H.; Wagner, R.; Tartar, J.; Melton, B. (International Journal of Exercise Science, 2020)
Sleep is an extremely important component for overall health and for a well-balanced training program. Recent studies have highlighted the interaction between sleep, recovery, and performance in elite and recreational athletes alike. Exercise has been known to affect the quality of sleep, nevertheless the impact is not well understood in the current research, particularly the effects of exercise timing and intensity on sleep quality. The purpose of this study was to understand if exercise timing and intensity significantly impact sleep quality among recreational exercisers. The participants involved were recreational exercisers who were self-grouped into an AM or PM exercise group. They participated in a seven-day quantitative, quasi-experimental, exploratory study wearing an Actigraph watch. The participant`s intensity was also self-grouped into moderate intensity or high intensity based on criteria cut points. Data was analyzed using a factorial ANOVA to examine if there was a significant difference between exercise timing and intensity on sleep quality of the participants. There were no significant differences in sleep quality in either the time group (AM vs PM) or the intensity group (MOD vs VIG) within the four measures of sleep that were looked at throughout this study; total sleep time, sleep onset latency, sleep efficiency % and wake after sleep onset (TST, SOL, SE, and WASO). Results within both, the AM and PM group and the MOD and VIG group, results showed no significant differences. These results conclude that neither exercise intensity or timing had an effect on sleep quality.